Cost‐effectiveness analyses of augmented cognitive behavioral therapy for pharmacotherapy‐resistant depression at secondary mental health care settings. Issue 11 (17th September 2021) - Sado, Mitsuhiro; Koreki, Akihiro; Ninomiya, Akira; Kurata, Chika; Mitsuda, Dai; Sato, Yasunori; Kikuchi, Toshiaki; Fujisawa, Daisuke; Ono, Yutaka; Mimura, Masaru; Nakagawa, Atsuo
Abstract : Aim: Pharmacotherapy is the primary treatment strategy in major depression. However, two‐thirds of patients remain depressed after the initial antidepressant treatment. Augmented cognitive behavioral therapy (CBT) for pharmacotherapy‐resistant depression in primary mental health care settings proved effective and cost‐effective. Although we reported the clinical effectiveness of augmented CBT in secondary mental health care, its cost‐effectiveness has not been evaluated. Therefore, we aimed to compare the cost‐effectiveness of augmented CBT adjunctive to treatment as usual (TAU) and TAU alone for pharmacotherapy‐resistant depression at secondary mental health care settings. Methods: We performed a cost‐effectiveness analysis at 64 weeks, alongside a randomized controlled trial involving 80 patients who sought depression treatment at a university hospital and psychiatric hospital (one each). The cost‐effectiveness was assessed by the incremental cost‐effectiveness ratio (ICER) that compared the difference in costs and quality‐adjusted life years, and other clinical scales, between the groups. Results: The ICERs were JPY −15 278 322 and 2 026 865 for pharmacotherapy‐resistant depression for all samples and those with moderate/severe symptoms at baseline, respectively. The acceptability curve demonstrates a 0.221 and 0.701 probability of the augmented CBT being cost‐effective for all samples and moderate/severe depression, respectively, at the threshold of JPY 4.57 million (GBP 30 000). The sensitivity analysis supported the robustness of our results restricting for moderate/severe depression. Conclusion: Augmented CBT for pharmacotherapy‐resistant depression is not cost‐effective for all samples including mild depression. In contrast, it appeared to be cost‐effective for the patients currently manifesting moderate/severe symptoms under secondary mental health care.